If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(5 + -1w) + 3(-2w) = 0 2 + (5 * -1 + -1w * -1) + 3(-2w) = 0 2 + (-5 + 1w) + 3(-2w) = 0 Remove parenthesis around (-2w) 2 + -5 + 1w + 3 * -2w = 0 Multiply 3 * -2 2 + -5 + 1w + -6w = 0 Combine like terms: 2 + -5 = -3 -3 + 1w + -6w = 0 Combine like terms: 1w + -6w = -5w -3 + -5w = 0 Solving -3 + -5w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5w = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -5w = 0 + 3 -5w = 0 + 3 Combine like terms: 0 + 3 = 3 -5w = 3 Divide each side by '-5'. w = -0.6 Simplifying w = -0.6
| 2n+5=4n+2-n | | 3p^2+3p-36=0 | | 9-30=6-p | | X+6(3)=42 | | 6w+36=3w | | 25.6=6.4xn | | 4a-2=3(1+x) | | 6x^2-528=0 | | -13=-3x+12 | | 20-48=10-p | | A+B=B+A | | g(7)=3x+6 | | -6(2-5v)=54 | | 5X-4+X=7-3X+5 | | a+a+5=0.5a+a | | 5(3x-2)-5(2x-16)=2(2x+5)-2 | | 4(f+2)=20 | | (33b-8)-8(4b+3)=-3 | | 1x+2=4 | | 5x+2=30 | | f(-8)=4x-2 | | x^3-12x^2+8x=0 | | 5n^2-180=0 | | 3.5q-2.8-3.3q=-0.8q-1.7 | | f(-10)=4x-2 | | -2(5s-3)-6=-3(9s+2)-4 | | 4x^3+16x^4-24x^2-9=0 | | -101+5x=186+12x | | 8n-6=11-9n | | 2=5x+12 | | 3b^2+6=11b | | -3y+9=-4y+1 |